Analysis of the Student Numerical Literacy in Completing the Division Count and Multiplication Operation of the 6th Grade Elementary School Round Number - Triwahyuningtyas, Dyah; Hanum, Abdila Ayu Hanna Mulya; Suastika, I Ketut; Sesanti, Nyamik Rahayu (Universitas Muhammadiyah Mataram, 2023)
The background of this study is that students are unable to solve the problems and problems of daily life and which of the students associated with literacy, are unable to think critically and be able to reason in understanding the concept of division operations and multiplication integers. The aim of this study was to describe numerical literacy in the division and multiplication operations of integers in 6th grade elementary school. Research type use descriptive with a qualitative approach. Research instrument consist of interview instrument, observation instrument, and test subject. Research has found no significant obstacle, the study subject can complete most numerical literacy components on the test issue. Research subjects has not been able to dominate numerical literacy of patterns and statistic intact, but some of the components appearing on the subject have not been fully resolved.